OPTIMIZATION OF CARBOPOL 940 AND PROPYLENE GLYCOL CONCENTRATION ON THE CHARACTERISTIC AND INHIBITORY EFFECT OF ETHANOL EXTRACT GEL OF PAPAYA (Carica papaya L.) SEEDS AGAINST Staphylococcus aureus - Octavianus Yandri; Wahyuning Setyani (Sanata Dharma University, 2021)
Papaya (Carica papaya L.) seeds contain alkaloids, flavonoids, tannins, phenolic compounds and saponins have been proven its synergistic effect in inhibiting the growth of Staphylococcus aureus. In this research, ethanol extract of papaya seeds was formulated in gel preparations. Optimization of the composition of the gelling agent and humectant was carried out to obtain the gel preparation of papaya seed ethanol extract with good physical properties and stability. The parameters used to determine the stability of the preparation are Physical properties which include viscosity, spreadability, and percentage of viscosity shift. Data analysis was performed using Design-Expert software version 12 and SPSS. The inhibitory activity test was carried out by the disk-diffusion agar method with Staphylococcus aureus ATCC 25923 as the test bacteria. The results of the inhibitory activity test of papaya seed ethanol extract at a concentration of 20% had moderate activity and at concentrations of 40%, 60%, 80% and 100% classified as strong against the Staphylococcus aureus. Carbopol 940 is dominant factor in influencing the response of viscosity (92.504%) and spreadability (59.539%). Preparations with good physical properties and stability were obtained on the use of carbopol 940 and propylene glycol as much as 1.06604 grams and 13.2146 grams respectively.